Analisis Peran KOMPAK dalam Meningkatkan Kesadaran Antikorupsi di Kalangan Pemuda di Bandar Lampung - Rizky Wahyudi; Anung Mabilla; Atika Sari Dewi; Rima Yuni Saputri; Ana Mentari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Youth plays a strategic role as agents of change in nation-building, including in efforts to eradicate corruption. This article analyzes the role of the Coalition of Society Concerned with Anti-Corruption (KOMPAK) in increasing anti-corruption awareness among young people. Through educational, empowerment, and capacity-building approaches, KOMPAK actively organizes seminars, workshops, social campaigns, and political education programs for youth in Lampung Province. This study uses observation and interview methods to explore KOMPAK’s programs and their impact on developing anti-corruption character among the younger generation. The analysis reveals that KOMPAK serves not only as a platform for raising awareness but also as a driving force for social change by instilling values of integrity, responsibility, and active participation. Therefore, KOMPAK's presence exemplifies the critical role of youth organizations in fostering a clean and accountable governance system.